2012
DOI: 10.5402/2012/952196
|View full text |Cite
|
Sign up to set email alerts
|

The Use of ISSR and RAPD Markers for Genetic Diversity among South Tunisian Barley

Abstract: Random amplified polymorphic DNA (RAPD) and intersimple sequence repeat (ISSR) were assayed to determine the genetic diversity of 80 barley specimens from South Tunisia. The ISSR primers showed variation in the percentage of polymorphism, band informativeness (Ib), and resolving power (Rp). The percentage of polymorphism is 66.67%, the average Ib ranged from 0.24 to 0.39, while Rp ranged from 0.74 to 1.16. In RAPD analysis, three primers yielded a total of 17 scorable bands, which are all polymorphic. The thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 37 publications
4
25
0
1
Order By: Relevance
“…According to Ajibade et al (2000) a high number of alleles and polymorphism are of great importance for the correct estimation of genetic diversity of any germplasm. The high polymorphic results in this work is in consonance with the work of Guasmi et al (2012) where 100% polymorphism was obtained in their use of RAPD markers to study the genetic diversity among South Tunisian barley. A total of 95 loci detected in this study showed that the markers are both effective and informative in the study of the molecular characterization of D. filamentosum.…”
Section: Discussionsupporting
confidence: 88%
“…According to Ajibade et al (2000) a high number of alleles and polymorphism are of great importance for the correct estimation of genetic diversity of any germplasm. The high polymorphic results in this work is in consonance with the work of Guasmi et al (2012) where 100% polymorphism was obtained in their use of RAPD markers to study the genetic diversity among South Tunisian barley. A total of 95 loci detected in this study showed that the markers are both effective and informative in the study of the molecular characterization of D. filamentosum.…”
Section: Discussionsupporting
confidence: 88%
“…The rapid detection is beneficial to check the homogeneity between mother and in vitro grown plantlets (Devarumath et al 2002). The PCR associated DNA molecular markers based analysis system such as Random amplified polymorphic DNA (RAPD), Amplified fragment length polymorphism (AFLP), Simple sequence Repeat (SSR), Inter-sequence simple repeats (ISSR) and microsatellite DNA/SSRs possess several benefits over the traditional methods that have been used for detection of polymorphism and genotyping in plant systems (Lal et al 2008; Guasmi et al 2012; Rajpal et al 2014). The RAPD and ISSR analysis has been widely used to determine polymorphism in genomic DNA in sugarcane and several other plant systems due to numerous advantages like being a relatively fast, simple, cost-effective technique which requires a small quantity of DNA sample with no preliminary sequence information for primer design (Suprasanna et al 2006; Devarumath et al 2007; Lal et al 2008; Rizvi et al 2012; Dangi et al 2014; Kshirsagar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous systems of molecular markers now available for population genetics studies. Inter simple sequence repeat (ISSR) analysis is an inexpensive system that requires relatively little time and effort for development of primer sets (Nybom 2004) that has been used successfully for genetic diversity assessment of numerous plant species (Godwin et al 1997;Blair et al 1999;Bornet et al 2004;Grativol et al 2011;Guasmi et al 2012).…”
Section: Introductionmentioning
confidence: 99%